FAKTOR- FAKT OR YANG MEMPENGARUHI KEPUASAN PELANGGAN PADA PT. PLN (Persero) WILAYAH SUMUT CABANG LUBUK PAKAM RANTING MEDAN DENAI - Simanihuruk, Peran (UNIKA Santo Thomas, 2010)
.ABSTRAK One of the State Electricity Company Owned Enterprises as the manager of the electricity transmission to provide a service that can meet the expectations of stakeholders and to contribute improvement of community welfare. One form of services provided by Payment Online Point Bank (PPOB). Aim to provide convenience to customers as well as healthy competition among service providers. But on the other hand also often cause dissatisfaction for customers such as online payment Qf electricity bills. Formulated the research problem: What factors inï¬‚uence customer satisfaction in the dominant PT. PLN (Persero) Region North Sumatra Medan Branch Branches Lubuk Pakam Denai. This study aims to determine and analyze the factors that aï¬bct customer satisfaction. Benqits of the research is to provide input to the PLN in order to provide a quality service. The study population was all PT customers. PLN (Persero) Region North Sumatra Medan Branch Branches Lubuk Pakam Denai. Sample of 125 respondents. Data collection techniques with questionnaires and documentation. Techniques of data analysis with factor analysis. The results and discussion show from the 25 variables obsemed prior to rotation there are 15 variables that have a correlation coejjficient above 0.5 setelahrotasi to 23 variables as the dominant factor affecting customer satisfaction. Of the 23 variables are grouped into eight factors: FACTOR 1 Understanding the customer needs, prompt service, friendliness of employees, Employee Attitude, a safe place of service and a sympathetic attitude. FACTOR 2: a genuine concern, timeliness of service and employee appearance. FACTOR 3: The equipment used and the speed of service, FACTOR 4: Response to complaints and handling problems, FACTOR 5: Caring stajji Presedur application and employee competence, FACTOR 6: I/Villingness to help employees, and recency of Conformity implementation tools, FACTOR 7: Information clear_ and the sense of security during the deal and FACTOR 8: Attention Patience qï¬icers and employees. Conclusion there are 23 variables as the dominant factor affecting customer satisfaction, namely: understanding customer needs, fast service, friendly staff, the attitude of employees, a safe place of service, a sympathetic attitude, genuine concern, timeliness of service, appearance of employees, equipment used , speed if service, responsiveness to complaints, deal with, caring staï¬‚i Presedur application and competence of employees, employee willingness to help, Compliance execution, currency ofâ€˜ equipment, clear information, sense of security during the deal, the attention of officers and employees Patience. While suggestions to improve the quality of service that quickly and accurately through training and employee development, disseminating a manual system with computerized equipment online payment of electricity bills to provide greater convenience for customers and establishing mutually beneï¬cial